2017
DOI: 10.1002/bio.3322
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2nanoparticles on some photophysical characteristics of ketocyanine dyes

Abstract: The effect of titanium dioxide (TiO ) nanoparticles (NPs) on photophysical characteristics of 2,5-di[(E)-1-(4-dimethylaminophenyl) methylidine]-1-cyclopentanone (2,5-DMAPMC) and 2,5-di[(E)-1-(4-diethylaminophenyl)methylidine]-1-cyclopentanone (2,5-DEAPMC) ketocyanine dyes has been studied using absorption, steady-state and time-resolved fluorescence spectroscopy. The magnitudes of association constants determined based on modified absorption spectrum of dyes due to the presence of TiO NPs indicate the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Due to the unique physicochemical properties and increased reactivity of nanoparticles, they might interfere with photometric and fluorometric assays, potentially leading to false positive or false negative results [167,168]. Nanoparticles may enhance or quench the fluorescence signals of the dyes, adsorb assays reagents, catalyze enzymatic reactions, or they might affect the measurements due to the intrinsic fluorescence [169][170][171][172]. Several studies reported interactions between nanoparticles e.g., carbon-based materials [173], and TiO2 nanomaterials [168,172] and test systems.…”
Section: Nanomaterials Interference With In Vitro Toxicity Assaysmentioning
confidence: 99%
“…Due to the unique physicochemical properties and increased reactivity of nanoparticles, they might interfere with photometric and fluorometric assays, potentially leading to false positive or false negative results [167,168]. Nanoparticles may enhance or quench the fluorescence signals of the dyes, adsorb assays reagents, catalyze enzymatic reactions, or they might affect the measurements due to the intrinsic fluorescence [169][170][171][172]. Several studies reported interactions between nanoparticles e.g., carbon-based materials [173], and TiO2 nanomaterials [168,172] and test systems.…”
Section: Nanomaterials Interference With In Vitro Toxicity Assaysmentioning
confidence: 99%